1989
DOI: 10.1002/ijc.2910430311
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between peripheral blood lymphokine‐activated killer (lak) cell function and clinical response in patients with advanced malignant melanoma receiving recombinant interleukin 2

Abstract: A phase-I/II study of recombinant interleukin 2 (rIL-2) was performed in 31 melanoma patients. The first dose of rIL-2 was given intrasplenically followed 4 hr later by an i.v. dose and 3 further i.v. doses on alternate days. Three courses of treatment were planned at 3-week intervals. The maximum tolerated single dose was 11 x 10(6) Cetus U/m2. Haematological and immunological data were available on 20 patients. Post-treatment response to rIL-2 therapy was evident from (i) a rapid depletion of peripheral bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
2

Year Published

1990
1990
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 24 publications
0
22
2
Order By: Relevance
“…FAA has been shown to have high anti-tumour activity and a possible host mediated mechanism of toxicity including augmentation of NK cell activity (Ching & Baguley, 1987; cancer. In our previous study of rIL-2 alone (Ghosh et al, 1989), increased NK activity was observed in 16 of 20 patients while on treatment. showed maximal NK cell activity in the peripheral blood of mice at 48 h, which persisted for 6 days after FAA administration.…”
Section: Lak Cell Precursorsmentioning
confidence: 75%
See 4 more Smart Citations
“…FAA has been shown to have high anti-tumour activity and a possible host mediated mechanism of toxicity including augmentation of NK cell activity (Ching & Baguley, 1987; cancer. In our previous study of rIL-2 alone (Ghosh et al, 1989), increased NK activity was observed in 16 of 20 patients while on treatment. showed maximal NK cell activity in the peripheral blood of mice at 48 h, which persisted for 6 days after FAA administration.…”
Section: Lak Cell Precursorsmentioning
confidence: 75%
“…This combined adoptive immunotherapy is, however, expensive and labour intensive, and toxicity is severe when high doses of IL-2 are used. In our previous phase I/II clinical trial of intrasplenic and intravenous rIL-2 less toxicity was achieved and partial clinical responses were observed in 15% of patients with progressing advanced melanoma (Thatcher et al, 1989). These encouraging results stimulated interest in using rIL-2 in combination with other biological response modifiers or with chemotherapeutic drugs in the hope that better clinical responses could be achieved.…”
mentioning
confidence: 94%
See 3 more Smart Citations